2000
DOI: 10.1007/s000180050036
|View full text |Cite
|
Sign up to set email alerts
|

Helicases and aging

Abstract: Studying monogenic hereditary disorders syndrome. A decline of probably pleiotropic and funthat manifest age-related phenotypes in cells, tissues, damental function of helicases in these disorders is, and the total organism would be helpful for clarifying therefore, implied to underlie not only the various agerelated phenotypes of the disorders but also the the mechanisms of aging. In this context, seven human disorders that manifest age-related phenotypes have pleiotropic and universal nature of ordinary agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 104 publications
(114 reference statements)
1
19
0
2
Order By: Relevance
“…It has been hypothesized that several WS phenotypes are secondary consequences of aberrant gene expression (6), and our results suggest that the same is the case for normal aging. The transcription process requires unwinding of the DNA duplex, and involvement of helicases in transcription is exemplified by the observation that one of the basal transcription factors, TFIIH, exhibits DNA unwinding activity (38).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It has been hypothesized that several WS phenotypes are secondary consequences of aberrant gene expression (6), and our results suggest that the same is the case for normal aging. The transcription process requires unwinding of the DNA duplex, and involvement of helicases in transcription is exemplified by the observation that one of the basal transcription factors, TFIIH, exhibits DNA unwinding activity (38).…”
Section: Discussionsupporting
confidence: 75%
“…The transcription process requires unwinding of the DNA duplex, and involvement of helicases in transcription is exemplified by the observation that one of the basal transcription factors, TFIIH, exhibits DNA unwinding activity (38). In addition to WS, six other segmental progeroid syndromes are caused by mutations in helicase genes, which implies contribution of aberrant helicases to phenotypes in normal aging (6). One of these is Cockayne syndrome (CS), in which we have demonstrated a transcription defect after hydrogen peroxide exposure (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the human RECQ helicases, BLM and WRN were shown to be the determinants of the Bloom and Werner syndrome, respectively (32,33), and two kindreds with Rothmund-Thomson syndrome were shown to segregate with mutations in RECQ4 (34). These RecQ helicase syndromes have been reported to exhibit genetic instability, and one of the clinical manifestations of Werner and Rothmund-Thomson syndromes patients is premature aging (35)(36)(37). Interestingly, sgs1 nulls also appear to exhibit a reduced lifespan, defined for the budding yeast as the total number of buds a mother cell can produce (38).…”
mentioning
confidence: 99%
“…In accordance with this finding it has been suggested that several phenotyical aspects WS are secondary consequences of aberrant gene expression (Nakura et al, 2000). Gene expression is changed to adapt to cellular stress (Lee et al, 1995;Moradas-Ferreira and Costa, 2000;Volkert and Landini, 2001;Kyng et al, 2003a;Moggs and Orphanides, 2003), and this adaptation is likely to be affected in aging because of constant exposure to cellular stress.…”
Section: Introductionmentioning
confidence: 81%